Nanosecond white-light Laue diffraction measurements of dislocation microstructure in shock-compressed single-crystal copper. - Suggit, M; Higginbotham, A; Hawreliak, J; Mogni, G; Kimminau, G; Dunne, P; Comley, A; Park, N; Remington, B; Wark, J (2012)
Under uniaxial high-stress shock compression it is believed that crystalline materials undergo complex, rapid, micro-structural changes to relieve the large applied shear stresses. Diagnosing the underlying mechanisms involved remains a significant challenge in the field of shock physics, and is critical for furthering our understanding of the fundamental lattice-level physics, and for the validation of multi-scale models of shock compression. Here we employ white-light X-ray Laue diffraction on a nanosecond timescale to make the first in situ observations of the stress relaxation mechanism in a laser-shocked crystal. The measurements were made on single-crystal copper, shocked along the [001] axis to peak stresses of order 50 GPa. The results demonstrate the presence of stress-dependent lattice rotations along specific crystallographic directions. The orientation of the rotations suggests that there is double slip on conjugate systems. In this model, the rotation magnitudes are consistent with defect densities of order 10(12) cm(-2).